Toddler Nutrition Status Monitoring Dashboard as A Support for Stunting Reduction Acceleration Program in Temanggung Regency - Naufal Dzaky Arrachman; Affan Safani Adam; Aprilia Hikari Tamira Jasmine; Agung Wardoyo; Karis Widyatmoko; Ibnu Utomo W.M.; Vilda Ana Veria Setyawati; Muhammad Iqbal; Ririn Nurmandhani; Firmansyah Kholiq Pradana P.H.; Eti Rimawati (Health Science UDINUS, 2024)
Temanggung Regency is the district with the second-highest prevalence ofstunting (28.9%) in Central Java. This result was still far from the nationalstunting prevalence target in 2024, which is 14%. Monitoring the nutritionalstatus of toddlers regularly is very necessary as an effort to carry out earlydetection in preventing stunting. Stunting reduction activities specifically atthe lower level are carried out by cadres. The role of the cadres includesmeasuring and recording the anthropometry of infants and toddlers. In thedata collection process, several problems were found including writing andcounting errors and delays in data distribution. To overcome this problem, acomputerized system is needed that can be used as a means of collecting dataon the nutritional status of toddlers quickly and in real-time. SI-GEMBULdashboard is the final result of reporting from SI-GEMBUL application whichis used by cadres to overcome problems with writing errors and calculatingthe nutritional status of toddlers. The system development method used inthis study was the prototyping method. SI-GEMBUL dashboard displayconsists of a list of mothers, infants, and toddlers that can be displayed byPosyandu name, a real-time checklist that can be displayed by year, month,and name of the Posyandu, as well as educational media related to nutritionand stunting. This dashboard can help the Temanggung District Health Officeto be able to minimize delays in the distribution of data that will be used forreporting to a higher level.